REALISM STILISTICS OF GENRE HORROR INDONESIAN MOVIES POST-REFORM: CASE STUDY OF FILM “KERAMAT” - Aji, Fajar (Capture : Jurnal Seni Media Rekam, 2018)
This article aims to describe the stylistic exploration of the ‘Keramat’ (‘Sacred’) film. Form and style are used as starting points to find out the exploration of stylistics film. Data information is identified based on similarities with the cinema movements that influence it. Subjectivity as an approach to the descriptive process by conducting interpretative analysis. The results showed that Cinema Verite and Italian Neorealism influenced the typical stylistic formula in the ‘Keramat’ film, especially supporting the characteristics of the horror genre including: creating a tense, frightening, and terror effect, also visualizing the concept of the realism of the events filmed.